1992
DOI: 10.1111/j.1365-2249.1992.tb03004.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibodies to human nerve antigens in sera from leprosy patients by ELISA

Abstract: SUMMARYAnti-neural antibodies have been implicated to play a role in the pathogenesis of nerve damage in leprosy patients. To find the relationship between anti-neural antibodies and clinical findings, we attempted to detect antibodies against iieurofilament-enriched proteins by ELISA in ,sera from leprosy patients. Of 2S9 sera frotn leprosy patients, 74 (256''..) had signilicant anti-neural antibodies; ineontrasl. 1 (50".,.) of 20 tuberculosis patients and II (71%) of 154 controls were seroreactive lo nerve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Autoimmune disorders of the ovary often cause ovarian dysfunction, resulting in irregularity of the menstrual cycle and infertility ( Nandedkar and Wadia, 1998 , Nelson et al, 2005 ). MB leprosy is often associated with an autoimmune phenomenon with various autoantibodies, such as anti-neutrophil cytoplasmic antibodies (ANCA), A-ANCA, anti-mitochondrial antibodies, and anti-phospholipid antibodies, found in the sera of patients ( Freire et al, 1998 , Garcia-De La Torre, 1993 , Guedes Barbosa et al, 1996 , Park et al, 1992 ). Hence, it has been suggested that autoantibodies directed against components of the ovary might be a cause of ovarian failure.…”
Section: Effect Of Leprosy On Menstrual Cycle and Fertility Statusmentioning
confidence: 99%
“…Autoimmune disorders of the ovary often cause ovarian dysfunction, resulting in irregularity of the menstrual cycle and infertility ( Nandedkar and Wadia, 1998 , Nelson et al, 2005 ). MB leprosy is often associated with an autoimmune phenomenon with various autoantibodies, such as anti-neutrophil cytoplasmic antibodies (ANCA), A-ANCA, anti-mitochondrial antibodies, and anti-phospholipid antibodies, found in the sera of patients ( Freire et al, 1998 , Garcia-De La Torre, 1993 , Guedes Barbosa et al, 1996 , Park et al, 1992 ). Hence, it has been suggested that autoantibodies directed against components of the ovary might be a cause of ovarian failure.…”
Section: Effect Of Leprosy On Menstrual Cycle and Fertility Statusmentioning
confidence: 99%
“…Interestingly, MB leprosy is often associated with autoimmune phenomenon, and a number of autoantibodies have been demonstrated . Several antibodies, for example anti‐neural antibodies, A‐ANCA, anti‐mitochondrial antibodies and anti‐phospholipid antibodies have been frequently demonstrated in the sera of patients with leprosy. Antibodies to spermatozoa have been reported in both LL and TT by highly specific techniques, but there was no correlation with type of leprosy .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, anti-peripheral nerve protein antibodies (both IgG and IgM) were rarely found in sera and did not correlate to disease activity or the pathogenesis of nerve damage [18]. In another study, antibodies to neurofilament-enriched proteins were detected more frequently, but still in only 30% of sera from lepromatous leprosy patients [19]: these were IgG antibodies which appear to predominate against proteins of molecular mass below around 40 kD [18,19].…”
Section: Methodsmentioning
confidence: 99%